Evaluation of insertion torque of different orthodontic miniscrews: An in vitro study - Al- Obaidi, Hussein Ahmed; Nadir, Mangur Maghdid (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: The purpose of this study was to evaluate the torque insertion for drill and non drill techniques of two commercially available miniscrews. Methods: Eighty mini screws (forty Dentos miniscrews/Korea and forty 3M miniscrews/USA), having the same length and diameter, were divided into two groups for each type. Two techniques, non-drill and drill, were used. In drill techniques, manufacturer recommended drill was used. Two bovine tibias were obtained. The first technique used pre drill hole, which was made in the bone using the recommended bur (1.0 diameter). The mini-screw was placed at 9 mm manually, then the remaining 1 mm was inserted through digital torque meter. The same procedure was repeated but without a pilot hole. Results: 3M miniscerws gave high torque insertion in two techniques. Conclusion: The shape, thread design and tip geometry of miniscerw play an important role in the torque insertion.